2021
DOI: 10.3390/ijms222212311
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Alterations in the Interplay of COVID-19 and Diabetes: Current Knowledge and Future Avenues

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (coronavirus disease 2019 [COVID-19]) pandemic has raged for almost two years, with few signs of a sustained abatement or remission [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In a word, a more personalized but comprehensive approach is needed instead of a “one-size-fits-all” intervention, different aspects of the diagnosis and therapy of dyslipidemia deserve to be mentioned in the era of contemporary medicine [ 25 ]. In the current world, with the COVID-19 pandemic, diabetes, obesity, and cardiovascular disease are related to an increased risk for severe forms of COVID-19 and resulting death, there is a direct effect of COVID-19 on the cardiovascular system and metabolic homeostasis, new markers reflecting the prognosis of cardiovascular disease need to be further explored [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a word, a more personalized but comprehensive approach is needed instead of a “one-size-fits-all” intervention, different aspects of the diagnosis and therapy of dyslipidemia deserve to be mentioned in the era of contemporary medicine [ 25 ]. In the current world, with the COVID-19 pandemic, diabetes, obesity, and cardiovascular disease are related to an increased risk for severe forms of COVID-19 and resulting death, there is a direct effect of COVID-19 on the cardiovascular system and metabolic homeostasis, new markers reflecting the prognosis of cardiovascular disease need to be further explored [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, as suggested by the American College of Cardiology Foundation, COVID-19 showed epidemiological and mechanistic relationships with cardiometabolic links [ 105 , 106 ] such as abnormal adiposity, dysglycemia [ 107 , 108 , 109 , 110 , 111 ], dyslipidemia, and hypertension [ 112 ]. In fact, COVID-19 caused an inflammatory response that might affect the cardiometabolic status.…”
Section: Cardiometabolic Connections In the Perio-covid-19 Axismentioning
confidence: 94%
“…It has been reported that endothelial dysfunction is very closely associated with COVID-19, and that this profound alteration may led to impaired organ perfusion and generating a number of acute events such as renal failure, myocardial injury, and procoagulant state, thus resulting in thromboembolic events [ 31 ]. Some authors have highlighted the pro-thrombotic potential of monocytes, and consequently the link with the prothrombotic state associated with SARS-CoV-2 infection [ 32 , 33 ]; indeed, the involvement of endothelial dysfunction in the pathogenesis of COVID-19 in patients with cardiometabolic diseases has been extensively investigated [ 34 ].…”
Section: Factors Related To Obesity That Predispose For Developing Co...mentioning
confidence: 99%